Post-marketing safety of solriamfetol: A retrospective pharmacovigilance study based on the us food and drug administration adverse event reporting system - Lingling Wu; Kaijian Zhu (PLoS ONE, 2025)
Purpose Excessive daytime sleepiness (EDS) seriously affects quality of life and may increase the risk of life-threatening situations, such as motor vehicle accidents. Solriamfetol is a novel medication approved for the treatment of EDS and serves as an alternative to traditional stimulants. This retrospective pharmacovigilance study aimed to analyze adverse events (AEs) related to solriamfetol based on real-world data. Methods Data regarding solriamfetol-related adverse events were retrieved from the FDA Adverse Event Reporting System (FAERS) from Q3 of 2019 to Q1 of 2024. A total of 1550 reports on solriamfetol-related AEs were analyzed using disproportionality analysis to identify AE signals across various organ systems. Results A large proportion of AEs were reported among female patients (64.06%), primarily including those with narcolepsy (38.13%) and obstructive sleep apnea (3.68%). The most frequently reported AEs included headache, anxiety, and drug ineffectiveness, with 46.8% of AEs occurring within 7 days of treatment initiation. Furthermore, solriamfetol was significantly associated with psychiatric and nervous system disorders as well as cardiac and general disorders. Conclusions Solriamfetol-related adverse events were mainly psychiatric, neurological, cardiac, and general disorders, with headache, anxiety, and drug ineffectiveness being the most common. Nearly half of the events occurred within the first week of treatment. Given the limitations of the FAERS database, further prospective studies are needed to confirm these findings.